2016
DOI: 10.1161/circresaha.115.306383
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Myocyte KLF5 Regulates Ppara Expression and Cardiac Function

Abstract: Rationale Fatty acid oxidation is transcriptionally regulated by peroxisome proliferator-activated receptor (PPAR)α and under normal conditions accounts for 70% of cardiac ATP content. Reduced Ppara expression during sepsis and heart failure leads to reduced fatty acid oxidation and myocardial energy deficiency. Many of the transcriptional regulators of Ppara are unknown. Objective To determine the role of Krüppel-like factor 5 (KLF5) in transcriptional regulation of Ppara. Methods and Results We discovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 69 publications
(99 reference statements)
5
79
1
1
Order By: Relevance
“…Strikingly, acute P2Y 6 In addition to JNK activation, we observed that P2Y 6 R stimulation resulted in downstream binding of cJUN to the PPARα promoter, thereby reducing PPARα transcription in white adipocytes. Such regulation of PPARα transcription by cJUN has also been reported in cardiomyocytes (53). We also demonstrated that JNK activation downstream of the P2Y 6 R regulates PPARα transcription, as treatment of cells with JNK inhibitor did not change Ppara mRNA levels.…”
Section: R Might Lead Tosupporting
confidence: 86%
“…Strikingly, acute P2Y 6 In addition to JNK activation, we observed that P2Y 6 R stimulation resulted in downstream binding of cJUN to the PPARα promoter, thereby reducing PPARα transcription in white adipocytes. Such regulation of PPARα transcription by cJUN has also been reported in cardiomyocytes (53). We also demonstrated that JNK activation downstream of the P2Y 6 R regulates PPARα transcription, as treatment of cells with JNK inhibitor did not change Ppara mRNA levels.…”
Section: R Might Lead Tosupporting
confidence: 86%
“…KLF5 can also be regulated by a variety of transcription factors and nuclear receptors, such as retinoic acid receptor α, nuclear factor κB, PPAR‐γ, and p300 . In our study, we found that H 2 S can decrease SP‐1 binding to the KLF5 promoter and thus suppress KLF5 expression.…”
Section: Discussionsupporting
confidence: 53%
“…KLF5 can also be regulated by a variety of transcription factors and nuclear receptors, such as retinoic acid receptor a, nuclear factor jB, PPAR-c, and p300. 26,27 In our study, we found that H 2 S can decrease SP-1 binding to the KLF5 promoter and thus suppress KLF5 expression. There are abundant exposed cysteine groups in the structure of SP-1, and it is possible that H 2 S may target SP-1 by S-sulfhydration.…”
Section: Discussionsupporting
confidence: 52%
“…These results indicate that dysregulation of mitochondrial dynamics can drive VSMC senescence and excessive ROS production. Although cardiomyocyte Klf5 was recently identified as a regulator of cardiac metabolism by directly activating transcription of PPARα and regulating lipid metabolism (Drosatos et al, 2016), whether and how Klf5 regulates mitochondrial dynamics is currently unclear.…”
Section: Introductionmentioning
confidence: 99%